Kendala Guru Bahasa Inggris dalam Pembelajaran Daring pada Masa Pandemi Covid-19 - Vebiyanti Nasir; Sariwati Muhamad (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to identificate the obstacles that the English Teacher faced in online learning and the solutions that teachers applied in solving the obstacles, also to identificate the method that the teachers used in teaching Grammar to students through online learning during pandemic Covid 19. Object of this study are 5 teachers of senior high school in Oba Utara Sub-District. A type of this study is qualitative, where is the data obtained from observation and interview. The data analysis carried out are raw data, organizing and preparing, reading through all the data, coding the data, description, and interpreting the meaning of description. The result of the study showed that the obstacles that the teacher faced are lack of internet network, limited of learning facilities such as handphone that students don’t have, the difficulty in teaching grammar by online, ineffective learning management, and learning assessment that is not appropriate with the assessment standard.